Tetraspanin, CD151, is required for maintenance of trigeminal placode identity - McCabe, Kathryn L. (2011)
The trigeminal ganglion is the largest of the cranial ganglia and responsible for transmitting sensory information for much of the face. The cell surface glycoprotein CD151 is an early marker of the trigeminal placode, the precursor to the ganglion. Here, we investigate the role of CD151 during specification of trigeminal placode cells in the developing chicken embryo. Expression of the transcription factor Pax3, the earliest known marker of the trigeminal placode, briefly precedes that of CD151, but they then subsequently overlap in the trigeminal placode. Loss of CD151 protein dramatically decreases the number of Pax3+ placode cells in stage 13-14 embryos, leading to loss of ophthalmic trigeminal neurons by stage 16-17. Although the initial size of the Pax3 population is similar to that in controls, the number of Pax3+ cells decreases with time without alterations in cell death or proliferation. This suggests a role for CD151 in maintenance of the specification state in the trigeminal placode, uncovering the first known role for a tetraspanin in a developmental system.